The citizen scientist: Community-academic partnerships through Translational Advisory Boards. Issue 12 (December 2016) - Patel, Darpan I.; Winkler, Paula; Botello, Jorge; Villarreal, Jocelin; Puga, Frank
Highlights: Engagement of minority populations into patient centered outcomes research. Citizen scientist are valuable contributors to addressing healthcare disparities. Equitable partnerships between the researchers and community is needed. Abstract: Objective: To describe the effectiveness of engaging patient partners as "citizen scientists" in the research process to boost patient centered outcomes research in underrepresented populations. Methods: Translational Advisory Boards in South Texas have effectively collaborated with University researchers to develop community-based patient centered research. Here we describe innovative approaches in research to engage patients and offer practical methods to enhance partnerships between patients and researchers to facilitate patient engagement. Results: Three health issues identified by the TABs were diabetes, obesity and teen pregnancy Examples of other community inspired research topics include air and water quality, methicillin-resistant staphylococcus aureus, intimate partner violence, chronic pain, and human papilloma virus and hepatitis C vaccinations. Conclusion: Patient engagement of underrepresented populations is inverse to the vast disparities they experience. In order to adequately address our nation's deficits in providing equitable healthcare, we must fully integrate disparate partners into the research process. By engaging community champions, academic health centers can fully integrate meaningful interventions on topics of interest to the catchment area in which they serve. Practice implications: These lessons can be used in developing local and regional collaborations across the country to boost active participation of patient stakeholder in PCOR to reduce healthcare disparities and improve our healthcare systems.